2009
DOI: 10.1038/nature08285
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization eliminates a roadblock during cellular reprogramming into iPS cells

Abstract: The overexpression of defined transcription factors in somatic cells results in their reprogramming into induced pluripotent stem (iPS) cells1–3. The extremely low efficiency and slow kinetics of in vitro reprogramming suggest that additional rare events are required to generate iPS cells. The nature and identity of these events, however, remain elusive. We noticed that the reprogramming potential of primary fibroblasts into iPS cells decreases upon serial passaging and the concomitant onset of senescence. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
645
3
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 784 publications
(690 citation statements)
references
References 29 publications
(46 reference statements)
38
645
3
4
Order By: Relevance
“…Only a few cells can overcome this barrier and become iPSCs. A number of studies demonstrated that when key components (such as p53 and p21) of the DNA damage pathway were deleted, the percentage of iPS cell generation significantly increased (Zhao et al, 2008a;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b). Suppression of the p53 pathway may compromise a cell's genome stability.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Only a few cells can overcome this barrier and become iPSCs. A number of studies demonstrated that when key components (such as p53 and p21) of the DNA damage pathway were deleted, the percentage of iPS cell generation significantly increased (Zhao et al, 2008a;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b). Suppression of the p53 pathway may compromise a cell's genome stability.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%
“…As the DNA damage pathway poses a major barrier towards regaining pluripotency (Zhao et al, 2008b;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b), chemical compounds that alleviate the stress of DNA damage response may help cells to overcome this barrier. To this end, Vitamin C has been shown to significantly increase the formation of both mouse and human iPSC by suppressing p53 induced cell senescence (Esteban et al, 2010).…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Thus, overexpression of this TF has profound and lasting consequences on the expression of growth-promoting genes. This process is influenced by the p53 status Kawamura et al, 2009;Mario´n et al, 2009;Utikal et al, 2009).…”
mentioning
confidence: 99%
“…Established GSCs from p53 knockout mice generate ES-like cells at a higher rate compared to wild-type, even after long periods in culture, indicating that p53 negatively controls the reprogramming process (Kanatsu-Shinohara et al, 2004). The importance of p53 activity has been confirmed in a series of publications describing enhanced iPS formation by p53 knockout or knockdown, although SSC reprogramming may not always take the same route before pluripotency is achieved (Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009). Genetic and epigenetic alterations of other tumor suppressors and cell cycle regulators are known to affect cell reprogramming and ES cell maintenance (Boominathan, 2009;Ruiz et al, 2011).…”
Section: Factors Affecting Reprogramming Efficiencymentioning
confidence: 97%